The Effect of Fixed Capital Investment, Consumer Price Index, and Small and Medium Enterprises (SMEs) on Economic Growth (GDP) in Kazakhstan - Tazhibayeva, R.M.; Kenzhebekova, I.P.; Sabenova, B.N.; Toktibayeva, M.Zh.; Keneshbayev, B.Zh. (BUKETOV BUSINESS REVIEW, 2023)
Object: The object of the research is the effect of Small and Medium Enterprises (SMEs) on economic growth in terms of three different variables. Methods: This research aims to analyze the effect of SMEs active in Kazakhstan on economic growth. For a better explanation, we also included fixed capital investments and the consumer price index in Kazakhstan in the research. We determined fixed capital investments, economic growth data, the Consumer Price Index (2000=100), the number of people employed by SMEs, the number of active SMEs, and the production of SMEs (Tenge) as the research variables. Research data was obtained from the database of the Bureau of National Statistics of the Agency of Strategic Planning and Reforms of the Republic of Kazakhstan. The data range is 2002-2020. Findings: The research findings showed that only the number of employees out of the three variables had a statis Conclusions: This result shows that the structuring and economic productivity of SMEs need to be examined in more detail within the framework of different variables.